Iran in antiquity: first mentions of Armenian-Iranian relations (part 1 - Media) - Zohrabyan, Eduard; Asryan, Vahagn (History and Culture, 2023)
For decades, in the scientific and socio-political discourse of Azerbaijan, the issues of the rights of Azerbaijanis living in the Islamic Republic of Iran have been widely discussed. This smoothly transforms into a pan-national idea – the reunification of the two Azerbaijans. This transformation constitutes a clear encroachment on the territory of the neighboring state. This issue becomes a subject of political speculation and is utilized by external forces – regional and non-regional countries, international institutions. The article presents the period when the first state formations appeared in the Iranian plateau and the rich Iranian culture and political life began to develop. The first part of this series of articles deals with the first Iranian state formation, Media, its historical course and decline. Taking into account that the history of the Armenian people is closely related to the history of the Medes, due attention was paid to the coverage of the Armenian-Medes historical relations. It is intended for Iranian scholars, historians, international scholars, teaching staff and students of universities, as well as the general reading public.
Keywords: Iran; civilizations; Media; dialogue; Urartu; geopolitics; Armenia; cultural heritage; Babylon; Mann; Lydia; Մանա; Լիդիա